Enhancing cultural competence in Malaysian nursing students - Mohamad Ismail, Mohamad Firdaus; Shaari, Nur Shuhada Ilmi; Mokhtar, Ahmad Effat; Shahadan, Siti Zuhaidah (IIUM Press, 2023)
Malaysia is a multi-racial country with Malay, Chinese, Indian, and other minor races. According to a recent statistic by the Department of Statistics Malaysia of 2022, the total population was 32.7 million, with 30.2 million Malaysian citizens and 2.4 million non-citizens. Malaysian citizens comprise of Bumiputera or Malays (69.9%), Chinese (22.8%), Indians (6.6%), and others (0.7%) (1). Every race holds unique perspectives and beliefs on various aspects of life, such as social, economic, spiritual, and health. However, it is essential to acknowledge that health is the most crucial aspect. The Ministry of Health (MOH) is responsible for providing citizens with high-quality healthcare services that align with the teachings of Chapter 5, Verse 32 of the Quran.